Chlorogenic acid: A promising natural agent for non-alcoholic fatty liver disease management - Honore, Stella Maris (2021)
Emerging and relatively consistent evidence shows that chlorogenic acid (CGA), a phenolic acid, positively modulates a variety of contributors to the non-alcoholic fatty liver (NAFLD) phenotype, through diverse and complementary mechanisms of action. Therefore, we believe that CGA is a good candidate for the management of NAFLD that deserves a review to aid future research.